Self Regulatory Drug Transport: An Intelligent Drug Delivery System - Ashish Jain; Pradeep Kumar Mohanty
ABSTRACT Introduction: Main objective of any pharmaceutical scientist is to develop drug delivery system that is safe, effective, stable, having good patient compliance and fulfill the requirements of customers. Lead to a great interest of research to develop the drug delivery system that will enable to supply drug «on-demand» basis. These «stimuli-responsive and intelligent» systems have been designed to deliver the drug on various times or at various sites in the body, according to a stimulus that is either endogenous or externally applied. Objectives: This paper aim to review various researches in the field of self regulatory drug delivery systems in tabular form so one can utilize these finding for further development of in intelligent drug delivery systems. Method: Various physicochemical principles and chemical schemes have been applied by researchers to get release pattern of drug as per requirement of body. Such devices can be used for intelligent drug delivery needed for the treatment of many diseases like diabetes. Results & Discussion: This type of intelligent system firstly sense the signals caused by diseaseà judge the magnitude of signalsà and then release the drug in direct response. Conclusion: In this article we have discuss various innovations in the field of self regulatory drug delivery Systems and suggest that here is a lot of research scope in this field.